A profile of the textile manufacturing industry - Parrish, Erin D., (Industry profiles collection., 2016)
The textile manufacturing industry (NAICS 313) has played an important role in the history of the United States and continues to be a major industrial employer, not only in the U.S., but also around the world. Textiles are mainly considered a component part of the supply chain, with end uses ranging from apparel to home textiles to industrial goods to medical textiles. Even though apparel is the largest end use of textiles and has increasingly moved offshore to low-cost labor countries, there remains a growing textile manufacturing industry in the U.S. for capital and technology-intensive products, such as nonwovens and those with military end uses. One unique aspect of textile manufacturing is that it includes sectors from agriculture, chemicals, industrial manufacturing, cutting-edge research and development, in addition to the fashion aspects of apparel and home goods. It is highly dependent on economic conditions and consumer demand, and competition is primarily based on price. Another unique aspect of the textile manufacturing industry is its fragmented nature. Whereas a few major players define most industries, there are over 8,000 textile establishments in the U.S., and no major textile firm has more than 2 percent share of the market. Also, unique to the textile industry is its importance in the global economy and to the economic development of other countries, particularly related to labor rights and women's issues. The textile manufacturing industry illustrates a variety of concepts including economics, technology and engineering, agriculture, history, marketing and fashion, globalization, social studies, labor issues, and environmental regulations, which would be useful to a number of audiences including students, industry, and public policymakers.